Collective-oriented collaboration: a grounded theory study of interprofessional practice in community based maternity care in Indonesia - Sulistyowati, Endah (2025)
This study explores interprofessional collaboration (IPC) among healthcare professionals (HCPs) in community-based maternity care settings in Indonesia, examining how they engage in collaborative practices and identifying the factors that influence their interactions. Despite global recognition of IPC’s benefits for enhancing patient care and outcomes, challenges persist, particularly in resource-limited settings where diverse professional roles intersect. Using a constructivist grounded theory approach, this qualitative study provides an in-depth understanding of collaborative dynamics by gathering insights from a range of HCPs engaged in maternity care at community health centres. Data were collected through online semi-structured interviews and document analysis. Initially, the study employed purposive, focused sampling of healthcare professionals involved in community maternity care, which then transitioned into theoretical sampling to explore and refine emerging categories as the analysis unfolded. A conceptual model, the “Collective Oriented Collaboration Model”, was developed to capture the complexity of community maternity services as the central challenge in IPC, with cross-sectoral collaboration serving as a critical means of managing this complexity. It acknowledges the significant role of the cultural values of “Gotong Royong” (mutual assistance) in shaping team collaboration, and three identified factors that affect IPC in this context: adaptive systems, value-based teamwork, and community empowerment. This grounded theory study adds to existing literature by highlighting the unique cultural and structural factors that affect IPC in community maternity settings in Indonesia. The study provides insights that are valuable for both local health policy and global discussions on collaborative practice in maternity care. This research offers a framework for understanding the complexities of interprofessional collaboration in community maternity care and supports future initiatives aimed at strengthening IPC in similar contexts.